Impact of Energy Consumption on Economic Growth in Major OECD Economies (1977-2014): A Panel Data Approach - Aali-Bujari, AlÃ; Venegas-MartÃnez, Francisco; Palafox-Roca, Omar (International Journal of Energy Economics and Policy, 2017)
This paper is aimed at assessing the impact of energy use growth on economic growth in the major economies of the Organization for Economic Cooperation and Development (OECD) during the period 1977-2014. To do this, a Granger causality analysis among relevant variables is carried out and, subsequently, a panel data model is estimated with the Generalized Method of Moments (GMM). The main empirical finding is that real GDP per capita growth is positively affected by the growth rate of energy use per capita in the following studied economies: Germany, Australia, Austria, Belgium, Canada, Denmark, Spain, USA, Finland, France, Greece, Holland, Italy, Luxembourg, Norway, Portugal, Sweden, and New Zealand. Keywords: energy consumption, economic growth, panel data analysis JEL Classifications: C23, O41, Q43